2020
DOI: 10.1186/s13690-020-00518-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of information, education, and communication with enrolment in health insurance: a case of Nepal

Abstract: Background Many studies indicate that various health programmes have been failed because of the lack of appropriate information, education, and communication [IEC] for the target audiences. It is still unanswered which methods/means of communication could be the most powerful for changing behaviour or decision-making capacity. The paper aims to assess the effects of IEC on family enrolment in health insurance programme [HIP] in Nepal. Methods We em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…This finding is similar to the observation made by previous study conducted in Baglung and Kailali districts of Nepal that reported a significant difference in terms of health insurance enrolment between groups based on access to health insurance messages through radio and TV. 45 This association may be due to the fact that households with members exposed to mass media have better access to the information regarding the enrolment process and future benefits the membership offers in terms of financial risk protection. 45 In Nepal, Brahmin, Chhetri, Madhesi, Janajati and Newar are considered upper and privileged caste in comparison Dalits and other ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is similar to the observation made by previous study conducted in Baglung and Kailali districts of Nepal that reported a significant difference in terms of health insurance enrolment between groups based on access to health insurance messages through radio and TV. 45 This association may be due to the fact that households with members exposed to mass media have better access to the information regarding the enrolment process and future benefits the membership offers in terms of financial risk protection. 45 In Nepal, Brahmin, Chhetri, Madhesi, Janajati and Newar are considered upper and privileged caste in comparison Dalits and other ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…45 This association may be due to the fact that households with members exposed to mass media have better access to the information regarding the enrolment process and future benefits the membership offers in terms of financial risk protection. 45 In Nepal, Brahmin, Chhetri, Madhesi, Janajati and Newar are considered upper and privileged caste in comparison Dalits and other ethnic minorities. Hindu and households from advantaged ethnic group were more likely to be registered with the health insurance schemes compared with non-Hindus and Dalits (including Muslims and ethnic minorities).…”
Section: Discussionmentioning
confidence: 99%
“…Health Insurance Act (HIA), which was enacted in 2017. According to the HIA, there is a mandatory provision that every citizen needs to enroll in the HIP, however, the act has not been fully operationalized (Acharya et al, 2020). Some private banking and financial institutions have been luring customers with the promise of providing different medical support schemes.…”
Section: Introductionmentioning
confidence: 99%
“…It may be the cause of inadequate knowledge and low satisfaction from HI programme and its functioning mechanism. Various factors associated with HI (Acharya, 2020); however, interaction with peers and neighbours appeared to influence enrollment (Acharya et al, 2020).…”
Section: Introductionmentioning
confidence: 91%